Pediatric flexible laryngoscopy: Trends in diagnostic abilities throughout training. (February 2020) - Maurrasse, Sarah E.; Li, Carol; Modi, Vikash K.
Abstract: Objectives: Our objectives were to evaluate the ability of residents to diagnose pathology of the pediatric larynx on laryngoscopy, to trend this ability throughout training, to compare their skills to pediatric otolaryngologists, and to determine whether reviewing digitally captured videos in slow motion, as opposed to a live exam, enhanced diagnostic abilities. In addition, we identified pathologies and anatomical sub-sites that posed diagnostic challenges. Methods: Qualtrics was used to design and distribute an online test, which included 15 pediatric laryngoscopy videos. Participants selected a diagnosis for each video after (1) watching it once at full speed and (2) watching the video multiple times in slow motion. Anonymous responses were exported into excel for statistical analysis, including T-test, ANOVA, and descriptive statistics. Results: There were 21 total participants. Median scores for full speed versus slow motion video review were 47% and 60% respectively. When analyzed by training level, there was no significant difference in scores for full speed videos, but there was a significant difference across groups for slow motion review (p = 0.04). Post Graduate Year (PGY) 4 residents and pediatric otolaryngologists performed best with an average of 69% and 77% respectively. Base of tongue, subglottic, and laryngeal cleft lesions were the most difficult to diagnose. Motor, laryngeal, and vallecular pathologies were more accurately identified. Conclusions: The ability to diagnose pathology on pediatric laryngoscopy tends to improve throughout residency training. Slow motion review enhances diagnostic skills. Laryngeal and vallecular pathologies are more easily diagnosed than base of tongue and subglottic lesions.